2016
DOI: 10.3109/0284186x.2016.1150607
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence in prostate cancer survivors

Abstract: Background High fear of cancer recurrence (FCR) is an understudied topic in prostate cancer (PCa) survivors. This study aimed to detect the prevalence, consequences and characteristics associated with high FCR in PCa survivors. Material and methods This cross-sectional study included patients diagnosed with localized PCa and treated with curative radical prostatectomy between 1992 and 2012. We administered the Cancer Worry Scale (CWS) to assess FCR severity (primary outcome measure). Secondary outcomes include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 24 publications
4
81
3
Order By: Relevance
“…Given that FOR is a common concern in prostate cancer, 17 in spite of good prognosis following treatment, it is important health care professionals have a greater understanding of factors that put survivors most at risk of lower well-being. Our previous work in this study population found that FOR is associated with type of treatment and regret over treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that FOR is a common concern in prostate cancer, 17 in spite of good prognosis following treatment, it is important health care professionals have a greater understanding of factors that put survivors most at risk of lower well-being. Our previous work in this study population found that FOR is associated with type of treatment and regret over treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that expectations regarding future disease course were related to survivor QOL is in keeping with a number of studies which have shown the important influence FOR has in determining QOL in prostate cancer. [14][15][16][17] We have shown that FOR acts independently of clinical variables such as cancer stage, number of comorbidities, treatment type, and side effects, in predicting QOL. The fact that FOR emerged overall as the strongest correlate of well-being clearly illustrates the pertinent relationship between prospective illness appraisals and well-being.…”
Section: The Importance Of Appraisals and Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that the spouses of people with prostate cancerpeople with cancer experienced more cancer worries than did the people and that they are considerably concerned about the disease, the effects and side effects of cancer treatment, changes in physical appearance and the impact of the cancer on their future (Oba et al, 2014). People who suffer from higher prostate cancer-specific anxiety experience a worse HRQOL (Mehnert, Lehmann, Schulte, & Koch, 2007;Nelson et al, 2016;van de Wal et al, 2016). Spouses who worried considerably about the recurrence of cancer among their spouse with prostate cancer demonstrate worse social functioning, emotional role functioning and mental health (van de Wal et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…complications of treatment, death from prostate cancer and cancer recurrence during the disease process (Oba et al, 2014;Tanner et al, 2011;van de Wal et al, 2016van de Wal et al, , 2017, more so for spouses of people with prostate cancer than people with cancer themselves (Oba et al, 2014). Further, the suicide rate of newly diagnosed people with cancer is 2.47 times higher than that of the general population (Lin et al, 2017).…”
mentioning
confidence: 99%